Fiscal Relations across Government Levels - Joumard, Isabelle (OECD Publishing, 2003)
Despite its apparent advantages, devolution of fiscal responsibilities has not proceeded evenly over the past two decades. Decentralisation can strengthen the democratic process, allow governments to tailor the supply of public goods to local preferences and introduce some competition across jurisdictions, thus raising public sector efficiency. It can, however, entail efficiency losses and make it difficult to implement redistributive policies. On the spending side, local provision may fail to exploit economies of scale and internalise territorial spillovers - a serious issue since few public goods are purely local by nature. On the revenue side, few tax bases can be exploited by sub-national governments without risking making national objectives difficult to achieve and raising serious distributive concerns. This paper, which is largely based on country experiences in mitigating the potential drawbacks of decentralisation while obtaining most of its benefits, provides a framework for assessing fiscal relations across levels of government...
Keywords: Economics